An Unusual Case of Giant Bullous Disease - Kenji Yoshino, MD; Jonathan Ioanitescu, MD; Haiying Zhang, MD; Tiana Endicott-Yazdani, MD, PhD; Susan K. Mathai, MD (CHEST Pulmonary)
Case Presentation: A 50-year-old African American woman presented to the lung transplant clinic for evaluation after experiencing gradually worsening dyspnea over the preceding 5 years. She had been diagnosed with COPD by another pulmonologist. Since her diagnosis 10 years before presentation, the patient had been on continuous supplemental oxygen therapy at 2 L/min. Her treatment regimen included a once daily combination inhaler (a corticosteroid and an ultra-long-acting ß-adrenoceptor agonist) along with an albuterol inhaler used as needed. The patient’s dyspnea limited her ability to walk half a block, and she often required a few minutes to recover after these efforts. Her symptoms were partially alleviated by use of her albuterol inhaler. In addition to dyspnea, the patient reported a nonproductive cough that was exacerbated by activity and relieved by rest. The patient’s medical history included OSA requiring positive airway pressure therapy and a hospitalization for respiratory distress due to a COVID-19 infection 12 months before presentation. She had a < 10-pack-year smoking history and childhood exposure to secondhand smoke. She had no known exposure to organic dusts or asbestos.